History and promotion of a culture of peace at global level through education - Kunal Mehta (Journal of Social Studies (JSS), 2020)
This article is concerned with the great task before the United Nations: saving future generations from the scourge of war. This entails the transformation not only of the institutional structures and manifestations of war, but also of the deeply rooted culture of violence and war, and the evolution of a culture of peace and non-violence. It provides a brief history of the concept of the culture of peace, discusses the basic aspects of the concept, and reflects on its relationship with everyday life. It then outlines the various actions undertaken by UNESCO during 1992–8 to promote a culture of peace, and lists declarations for a culture of peace and non-violence.